2021
DOI: 10.3390/nu13082850
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Portfolio Diet Score and Its Concurrent and Predictive Validity Assessed by a Food Frequency Questionnaire

Abstract: The Portfolio Diet, a plant-based portfolio of cholesterol-lowering foods, has been shown to reduce low-density lipoprotein cholesterol (LDL-C), and other cardiovascular risk factors, in randomized controlled trials (RCTs). It is not known if these beneficial effects translate to a lower incidence cardiovascular disease (CVD) risk. To support examinations between Portfolio Diet adherence and disease, a Portfolio Diet score (PDS) was developed and its predictive and concurrent validity was assessed within the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
(83 reference statements)
0
11
0
Order By: Relevance
“…Although the present study has not demonstrated the long-term benefit of the Portfolio Diet in reducing mortality risk due to CVD, further recent analyses revealed the prospective benefit of the adherence to the Portfolio Diet on cardiometabolic health. Higher adherence to the PDS was associated with lower LDL-C in the Toronto Healthy Diet Study [8], as well as with improvements in cardiometabolic risk factors, including glycated hemoglobin, fasting plasma glucose, triglycerides, waist circumference and BMI, in the PREDIMED-Plus cohort [9].…”
Section: Comparison With Previous Literaturementioning
confidence: 93%
See 2 more Smart Citations
“…Although the present study has not demonstrated the long-term benefit of the Portfolio Diet in reducing mortality risk due to CVD, further recent analyses revealed the prospective benefit of the adherence to the Portfolio Diet on cardiometabolic health. Higher adherence to the PDS was associated with lower LDL-C in the Toronto Healthy Diet Study [8], as well as with improvements in cardiometabolic risk factors, including glycated hemoglobin, fasting plasma glucose, triglycerides, waist circumference and BMI, in the PREDIMED-Plus cohort [9].…”
Section: Comparison With Previous Literaturementioning
confidence: 93%
“…The total points were then added for each respondent, resulting in a score range between 6 and 30, with higher scores indicating higher adherence to the Portfolio Diet. The adherence score of Portfolio Diet has been validated in 652 participants in the Toronto Healthy Diet Study, which has shown inverse association with lower LDL-C, and showed reasonable agreement between the score from the FFQ and 7-day dietary record [8].…”
Section: Dietary Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…19,21,22 Conversely, in addition to lipid-lowering medications, circulating cholesterol levels can be reduced through dietary intervention that promotes a portfolio of lipid-lowering foods such as vegetable proteins, viscous fibres, plant sterols and nuts. [24][25][26] A score evaluating the adherence to a plant-based cholesterol-lowering portfolio diet has been recently developed 27 and it has been correlated with reduced risk of cardiovascular disease. 28 However, this score includes items (e.g., peanut butter, okra, oats) that are not staple foods in many diets around the world, limiting its use.…”
Section: Introductionmentioning
confidence: 99%
“…A score evaluating the adherence to a plant-based cholesterol-lowering portfolio diet has been recently developed 27 and it has been correlated with reduced risk of cardiovascular disease. 28 However, this score includes items ( e.g.…”
Section: Introductionmentioning
confidence: 99%